Stabilitas Bangunan Sea Wall Pantai Sumare Kabupaten Mamuju - Irma Ridhayani (BANDAR: JOURNAL OF CIVIL ENGINEERING, 2021)
Sumare Village Beach has many residential areas located around the coast. The current condition is that many residential areas are located 1-2 m from the coastline and every year when the west season arrives the wave height reaches 2-3 m resulting in abrasion and erosion along the coastline. To handle this, a sea wall building is planned for Sumare Beach and one of the important items is the stability of the Sea Wall construction. The analysis was performed from the existing wave count data with a 25 year return period which aims to obtain the dimensions of the Sea Wall. After obtaining the dimensions, the stability of the building against shear, rolling and bearing capacity will be calculated. The results of this analysis obtained Sea Wall elevation height ± 3.84 m, Sea Wall peak width 1.94 m, Toe Protectin height 1.00 m and Toe Protection width 2.3 m. Stability analysis in normal conditions stability to rolling SF = 15.28> 2 shear SF = 4.5> 2 and soil bearing capacity σmax = 12,10 t/m2 < 112,71 t/m2 and 6,30 t/m2 > 0, and stability analysis in earthquake conditions stability to rolling SF = 5.88> 2 shear SF = 5.65> 2, and soil bearing capacity σmax = 8,51 t/m2 < 112,71 t/m2 and 9.89 t / m2> 0